Chemotherapy in Ewing’s sarcoma - Jain, Sandeep (Medknow Publications, 2010)
Ewing’s sarcoma constitutes three per cent of all pediatric malignancies. Ewing’s sarcoma has generally been more responsive to chemotherapy than adult-type sarcomas, and chemotherapy is now recommended for all patients with this disease. It is essential to integrate local control measures in the form of surgery and/or radiotherapy at the appropriate time, along with chemotherapy to eradicate the disease. This approach has improved the survival substantially to the tune of 70% in localized disease, although outcome for metastatic disease remains dismal. Newer therapeutic approaches are required to improve outcome for metastatic and recurrent or refractory Ewing’s sarcoma in organized co-operative group trials.